Asymmetric Transfer Hydrogenation of Heterocyclic Compounds in Continuous Flow Using an Immobilized Chiral Phosphoric Acid as the Catalyst - Zhelavskyi, Oleksii; Jhang, Yin-Jia; Nagorny, Pavel (Synthesis, 2023)
This manuscript describes transfer hydrogenation of bicyclic nitrogen-containing heterocyclic compounds using the immobilized chiral phosphoric acid catalyst (R)-PS-AdTRIP in batch and continuous flow. A significant improvement in enantioselectivities is achieved in continuous flow with a fluidized bed reactor packed with (R)-PS-AdTRIP when the flow rate is increased from 0.2 mL/min to 2.0–2.5 mL/min. The optimized continuous flow conditions consistently provide 4–6% ee higher selectivity than transfer hydrogenation in batch with 2 mol% of (R)-PS-AdTRIP, and are used to generate multiple chiral products with the same fluidized bed reactor.
Keywords: transfer hydrogenation; chiral phosphoric acid; continuous flow; enantioselectivity; heterocycles